Establishment of an efficient in vitro propagation system for Iris sanguinea. Issue 1 (December 2018) - Wang, Ling; Du, Yu; Rahman, Md.; Tang, Biao; Fan, Li-Juan; Kilaru, Aruna
Abstract Iris sanguinea is a perennial flowering plant that is typically cultivated through seeds or bulbs. However, due to limitations in conventional propagation, an alternate regeneration system using seeds was developed. The protocol included optimization of sterilization, stratification and scarification methods as iris seeds exhibit physiological dormancy. In addition to chlorine-based disinfection, alkaline or heat treatment was used to break seed dormancy and reduce contamination. When seeds were soaked in water at 80 °C overnight, and sterilized with 75% EtOH for 30 s and 4% NaOCl solution for 20 minutes, contamination was reduced to 10% and a 73.3% germination was achieved. The germinated seedlings with 2-3 leaves and radicle were used as explants to induce adventitious buds. The optimal MS medium with 0.5 mg L−1 6-benzylaminopurine, 0.2 mg L−1 NAA, and 1.0 mg L−1 kinetin resulted in 93.3% shoot induction and a proliferation coefficient of 5.30. Medium with 0.5 mg L−1 NAA achieved 96.4% rooting of the adventitious shoots. The survival rate was more than 90% after 30 days growth in the cultivated matrix. In conclusion, a successful regeneration system for propagation ofI. sanguinea was developed using seeds, which could be utilized for large-scale propagation of irises of ecological and horticultural importance.